Health care providers' adherence to tobacco treatment for waterpipe, cigarette and dual users in Vietnam. (January 2017) - Shelley, Donna; Kumar, Pritika; Lee, Lawrence; Nguyen, LinhThi; Nguyen, Trang Thi; VanDevanter, Nancy; Cleland, Charles M.; Nguyen, Nam Truong
Abstract: Background: Almost half of adult men in Vietnam are current cigarette smokers. Recent surveys also suggest a high prevalence of water pipe use, particularly in rural areas. Yet services to treat tobacco dependence are not readily available. The purpose of this study was to characterize current tobacco use treatment patterns among Vietnamese health care providers and factors influencing adherence to recommended guidelines for tobacco use screening and cessation interventions for water pipe, cigarette and dual users. Methods: We conducted cross sectional surveys of 929 male current tobacco users immediately after they completed a primary care visit at one of 18 community health centers. Results: Thirty-four percent of smokers used cigarettes only, 24% water pipe only, and 42% were dual users. Overall 12% of patients reported that a provider asked them if they used tobacco products during the visit. Providers were significantly more likely to screen cigarette smokers compared with water pipe or dual users (16%, 9% and 11% respectively). Similarly, 9% of current cigarette smokers received advice to quit compared to 6% of water pipe and 5% of dual users. No patients reported that their health care provider offered them assistance to quit (e.g., self-help materials, referral). Conclusion: Despite ratifying the Framework Convention on Tobacco Control, Vietnam has not made progress in implementing policies and systems to ensure smokers are receiving evidence-based treatment. High rates of water pipe and dual use indicate a need for health care provider training and policy changes to facilitate treatment for both cigarette and water pipe use. Graphical abstract: Highlights: Thirty-four percent of smokers in Vietnam used cigarettes only, 25% used water pipe only, and 41% were dual users. Only 9% of current cigarette smokers received advice to quit compared to 6% of water pipe and 4% of dual users. Providers were significantly more likely to screen cigarette smokers compared with Water pipe users and more likely to offer advice to quit to cigarette smokers compared with dual users. Providers are not only missing opportunities to offer effective cessation treatment to cigarettes users but may be even less likely to address the use of alternative tobacco products. There is a need for provider training that includes education about the harms of water pipe use and how to screen and offer brief advice and counseling that can address tobacco use across the full range of products.